Legal Assistance of the Justice Seeking Community through the Legal Aid Postal Service at the Pasarwajo Religious Court - safrin salam; Rizki Mustika Suhartono; La Ode Muhammad Karim; Siti Nur Anisa; Sri Mayanti (Universitas Muhammadiyah Malang, 2022)
Keberadaan Lembaga Bantuan Hukum dalam mewujudkan keadilan yang berpihak pada masyarakat keadilan sangat penting di Negara Indonesia. Salah satu perwujudan itu diwujudkan dalam bentul Pemberian Layanan bantuan hukum yakni Pos Bantuan Hukum di Pengadilan Agama Pasarwajo. Kegiatan ini merupakan bentuk pengabdian kepada masyarakat antara dosen fakultas hukum, Yayasan Lembaga Bantuan Hukum Amanah Peduli Kemanusiaan yang bermitra dengan Pengadilan Agama Pasarwajo dalam pemberian bantuan hukum kepda masyarakat miskin. Pada dasarnya, Posbakum Pengadilan Agama Pasarwajo telah menerapkan dan melaksanakan ketentuan yang ada dalam Perma Nomor 1 Tahun 2014 jo. SOP Pelayanan Pos Bantuan Hukum (POSBAKUM) Pengadilan Agama Pasarwajo No : SOP/AS/02 Tanggal 2 sedangkan peran Posbakum Pengadilan Agama Pasarwajo ada 4 yakni a) Memberikan bantuan hukum secara prodeo menurut UU 16 Tahun 2016 dan Perma No. 1 Tahun 2014; b) Memberikan akses keadilan bagi masyarakat yang kurang mampu terhadap pelayanan pengadilan; c) Melaksanakan asas peradilan yang cepat, murah dan biaya ringan; d) Mewujudkan peradilan yang agung sebagai mitra dari pengadilan agama pasarwajo. Legal Assistance of the Justice Seeking Community through the Legal Aid Postal Service at the Pasarwajo Religious Court The existence of legal aid institutions in realizing justice in favor of the justice community is very important in the State of Indonesia. One of the manifestations is manifested in the form of providing legal aid services, namely the Legal Aid Post at the Pasarwajo Religious Court. This activity is a form of community service between law faculty lecturers and The Amanah Peduli Humanitarian Legal Aid Foundation (YLBH ALIM), in partnership with the Pasarwajo Religious Court, in providing legal assistance to the poor. Basically, the Pasarwajo Religious Court Posbakum has implemented and implemented the provisions contained in Perma Number 1 of 2014 jo. SOP for Legal Aid Postal Services (POSBAKUM) of the Pasarwajo Religious Court No. SOP/AS/02 dated two while the roles of Posbakum for the Pasarwajo Religious Court are 4, namely a) Providing legal assistance on a free basis according to Law 16 of 2016 and Perma No. 1 of 2014; b) Providing access to justice for underprivileged communities to court services; c) Implementing the principle of fast, low-cost and low-cost justice; d) Realizing a great judiciary as a partner of the Pasarwajo.